Penggunaan Kurikulum Darurat dalam Meningkatkan Kualitas Pembelajaran Pada Masa Pandemi Covid-19 - Primanita Sholihah Rosmana; Sofyan Iskandar; Intan Dwi Yanti; Alya Zhulfarani; Fanny Rahmasari; Vika Ikram Nurfadhilah (AS-SABIQUN, 2022)
The curriculum is the most important part of the field of education, if there is no curriculum, learning may not be carried out properly. In this Covid-19 pandemic, the government through the Ministry of Education and Culture is working to ensure that learning can run well even though learning can be carried out online. The latest policy issued by the government is an emergency curriculum in education units under special conditions. The emergency curriculum is a simplification of the existing curriculum without reducing the substance and learning itself. The implementation of the emergency curriculum during the Covid-19 pandemic had a good influence on learning activities. Learning is a learning activity that is facilitated by teachers so that it can improve and develop cognitive aspects that improve thinking power and increase students' knowledge. The respondents in this study were shown to students, students, teachers and lecturers. This study aims to explore information regarding the use of the emergency curriculum in improving the quality of learning during the Covid-19 pandemic. The data collection technique used is through an e-questionnaire with google forms. The results of the study can show that the emergency curriculum can improve the quality of learning during the Covid-19 pandemic.